2017
DOI: 10.1371/journal.pone.0189511
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and antigenic divergence in the influenza A(H3N2) virus circulating between 2016 and 2017 in Thailand

Abstract: Influenza virus evolves rapidly due to the accumulated genetic variations on the viral sequence. Unlike in North America and Europe, influenza season in the tropical Southeast Asia spans both the rainy and cool seasons. Thus, influenza epidemiology and viral evolution sometimes differ from other regions, which affect the ever-changing efficacy of the vaccine. To monitor the current circulating influenza viruses in this region, we determined the predominant influenza virus strains circulating in Thailand betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 39 publications
6
28
0
Order By: Relevance
“…Influenza is prevalent throughout the year in some countries with tropical climate [6]. In Thailand, increased influenza activity appears biannually typically in the rainy (June-August) and cool (December-February) seasons [20,23,28]. Our multi-year study confirmed the substantial decrease in influenza activity following the relatively hot and dry month of May, which precedes the rainy season and coincides with the yearly recommended influenza vaccination period in Thailand [40,41].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Influenza is prevalent throughout the year in some countries with tropical climate [6]. In Thailand, increased influenza activity appears biannually typically in the rainy (June-August) and cool (December-February) seasons [20,23,28]. Our multi-year study confirmed the substantial decrease in influenza activity following the relatively hot and dry month of May, which precedes the rainy season and coincides with the yearly recommended influenza vaccination period in Thailand [40,41].…”
Section: Discussionsupporting
confidence: 74%
“…From January 2010 to December 2018, 30,852 nasopharyngeal or throat swab samples from patients with influenza-like illness (ILI) from Bangpakok 9 International Hospital (latitude 13.75˚N and 100.55˚E longitude) in Bangkok were analyzed as part of an ongoing influenza surveillance [23,28]. We defined ILI as fever >38˚C accompanied by cough and/or sore throat.…”
Section: Laboratory Testing Of Influenza Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Kilifi between 2009 and 2017 using full-length HA sequences. The presence of several antigenic site mutations among A(H3N2) virus strains circulating between 2009 and 17 influenza seasons confirms the continuing evolution of circulating strains in Kilifi, Kenya.Most of the amino acid variations associated with the continuing evolution of A(H3N2) viruses in Kilifi, Kenya have also been reported in other A(H3N2) viruses isolated in Africa, for example, in Cameroon36 and Mozambique,37 and in Asia, for example, in Thailand 38. Thus, the continuing evolution of A(H3N2) in Kilifi is inF I G U R E 3 A maximum likelihood phylogenetic tree of the HA gene segment for 66 KHDSS outpatient influenza A(H3N2) virus specimens collected from influenza surveillance in coastal Kenya, 2015-17.…”
mentioning
confidence: 69%
“…Thus, the mutation rate of the H3N2 viruses during the 2014–2016 epidemic seasons was much higher than that of the H1N1 viruses in China. Genetic surveillance of the H3N2 viruses from 2014 to 2016 indeed showed multiple substitutions in the antigenic sites and reassortant events worldwide ( Skowronski et al, 2016 ; Valenciano et al, 2016 ; Goldstein et al, 2017 ; Ma et al, 2017 ; Monamele et al, 2017 ; Suntronwong et al, 2017 ; Korsun et al, 2018 ). More importantly, the non-subtyped H3N2 strains using the Luminex RVP assay in this study were further subjected to genetic sequencing, and the occurrence of mutations and reassortment was verified (unpublished data, not shown).…”
Section: Discussionmentioning
confidence: 99%